TREATMENT RESULTS OF PATIENTS WITH COMPLICATED COLORECTAL CANCER IN ORDINARY HOSPITAL AND HOSPITAL ON REGIONAL LEVEL - S. N. Shchaeva; D. V. Narezkin (Вестник хирургии имени И.И. Грекова)
The article analyzed the results of surgical treatment of 1098 patients with urgent complications of colon cancer (acute intestinal obstruction, enterorrhagia, perforation, perifocal inflammation) in patients from Smolensk and Smolensk Region at the period from 2001 to 2013. The volume of surgical intervention depended on the age of patients, terms of hospital admission from the moment of complication development, common condition of patients, presence of severe accompanying pathology, localization of malignant tumor, presence of locally advanced process, regional metastasis, kind of urgent complication.